Anisotropic in-plane spin splitting in an asymmetric (001) GaAs/AlGaAs quantum well - Zhang Xiuwen; Ye Huiqi; Hu Changcheng; Wang Gang; Zhao Hongming; Tian Haitao; Wang Wenxin; Liu Baoli (Nanoscale Research Letters, 2011)
Abstract The in-plane spin splitting of conduction-band electron has been investigated in an asymmetric (001) GaAs/Al x Ga1-x As quantum well by time-resolved Kerr rotation technique under a transverse magnetic field. The distinctive anisotropy of the spin splitting was observed while the temperature is below approximately 200 K. This anisotropy emerges from the combined effect of Dresselhaus spin-orbit coupling plus asymmetric potential gradients. We also exploit the temperature dependence of spin-splitting energy. Both the anisotropy of spin splitting and the in-plane effective g-factor decrease with increasing temperature. PACS: 78.47.jm, 71.70.Ej, 75.75.+a, 72.25.Fe,